Phosphorylation of pRb by cyclin D kinase is necessary for development of cardiac hypertrophy - Hinrichsen, R. (Cell Prolif, 2008)
Abstract.  Objectives: A number of stimuli induce cardiac hypertrophy and may lead to cardiomyopathy and heart failure. It is believed that cardiomyocytes withdraw from the cell cycle shortly after birth and become terminally differentiated. However, cell cycle regulatory proteins take part in the development of hypertrophy, and it is important to elucidate the mechanisms of how these proteins are involved in the hypertrophic response in cardiomyocytes. Materials and methods, and Results: In the present study, by immunohistochemistry with a phosphorylation‐specific antibody, we found that cyclin D‐cdk4/6‐phosphorylated retinoblastoma protein (pRb) during hypertrophy and expression of an unphosphorylatable pRb mutant impaired hypertrophic growth in cardiomyocytes. Transcription factor E2F was activated by hypertrophic elicitors but activation was impaired by pharmacological inhibition of cyclin D‐cdk4/6. Inhibition of cyclin E‐cdk2 complex only partly impaired E2F activity and did not prevent hypertrophic growth, but diminished endoreplication during hypertrophy. Conclusions: These results indicate that cyclin D‐cdk4/6‐dependent phosphorylation of pRb and activation of E2F is necessary for hypertrophic growth in cardiomyocytes, whereas cyclin E‐cdk2 kinase is not necessary for hypertrophy but regulates endoreplication in these cells. The data support the notion that hypertrophic growth of cardiomyocytes involves a partial progression through the G(1) phase of the cell cycle.